Intravitreal Ranibizumab With Panretinal Photocoagulation Followed by Trabeculectomy Versus Visco-Trabeculotomy in Management of Neovascular Glaucoma. Issue 4 (July 2019) - Elwehidy, Ahmed S.; Bayoumi, Nader Hussein Lotfy; Badawi, Amani E.; Hagras, Sherein M.; Abdelkader, Amr
Abstract : Purpose: The aim of the current study was to compare visco-trabeculotomy (VT) with standard trabeculectomy with mitomycin C (Trab-MMC) in the treatment of quiescent neovascular glaucoma (NVG). Methods: The study was conducted on 51 eyes of 51 patients presenting with NVG and treated at an Ophthalmic Center in Egypt between March 2014 and April 2017. All study eyes were subjected to a standard protocol of intravitreal injection of ranibizumab followed by panretinal photocoagulation. Eyes were then randomized to either VT or Trab-MMC. Study eyes were followed up for at least 18 months. Success was defined as an intraocular pressure of ⩽21 mm Hg and without vision-threatening complications. Complications were noted. Results: The mean ± SD (range, median) age of the study patients was 54.1 ± 6.4 (40–67, 54.5) and 52.4 ± 8.8 (38–66, 53) years in the VT (26 eyes) and Trab-MMC (25 eyes) groups, respectively ( P = 0.45). The mean ± SD (range, median) intraocular pressure (IOP) of the study eyes was 45.19 ± 2.97 (39–52, 45.5) and 45.64 ± 3.56 (3–53, 45) mm Hg on maximal medical therapy in the VT and Trab-MMC groups, respectively ( P = 0.61). At 18 months' follow-up, the mean ± SD (range, median) IOP of the study eyes was 18.19 ± 2.0 (16–23, 17) and 19.92 ± 2.6 (18–26, 19) mm Hg in the VT and Trab-MMC groups, respectively ( P = 0.004). There was no difference in postoperative antiglaucoma medication between the 2 groups ( P = 0.62). Complications included hyphema and Descemet split in the VT group and an IOP spike in the Trab-MMC group. Success rates were 84.6% and 80% in the VT and Trab-MMC groups, respectively ( P = 0.726). Conclusions: Both VT and Trab-MMC groups are effective in reducing the IOP in cases of NVG after control of neovascularization with anti-vascular endothelial growth factor and pan retinal photocoagulation.